KONSTRUKSI TELEVISI LOKAL BAGI PELAKU TELEVISI LOKAL (Studi Fenomenologi pada stasiun TV lokal Megaswara Bogor) - Feri Ferdinan Alamsyah; Muslim - (Universitas Pakuan, 2019)
AbstrakLocal television stations have a mission to provide a variety of shows to local communities in the broadcast local area. This diversity is intended to against the potential influence of national television station shows that tend to be centralized. In practice, local television stations face a number of very difficult obstacles. Through qualitative research methods with a phenomenological approach, this study explains the position of local television stations in responding to the development of regulations and the technology they experience. This study resulted that as a broadcast media, local TV stations have very heavy barriers, such as the obscurity of broadcasting regulations, the development of broadcast technology, competition with other mediums that are developing, and internal conditions of the company. To be able to survive, a television station needs to adapt to the development of the times, the television concept was then developed in a collaborative form that is not always based on the audio visual broadcast context. For example by forming radio broadcasts and optimizing the agenda off the air or outside the broadcast.